2015
DOI: 10.5505/agri.2015.37167
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of compensatory hyperhidrosis of the trunk with radiofrequency ablation

Abstract: SummaryObjectives: Although Endoscopic Thoracic Sympathectomy is a widely accepted treatment method for patients with palmar hyperhidrosis, compensatory hyperhidrosis of the trunk remains a challenging side effect of the procedure. No satisfactory treatment options for this side effect were available until now. In this study, we aimed to define a new procedure for the treatment of compensatory hyperhidrosis of the trunk. Methods: A total of 10 patients admitted our institution for the treatment of compensatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We assumed that CH occurs though the remaining sympathetic chains from the hypothalamic reflex arc. This assumption was reasonably demonstrated in some studies, which showed that CH was limited in the lower body when sympathicotomy was expanded to R7 and thoracic sympathicotomy improved CH in the trunk when CH developed after sympathicotomy (10,28,29). Therefore, we designed an expanded sympathicotomy technique to reduce CH.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We assumed that CH occurs though the remaining sympathetic chains from the hypothalamic reflex arc. This assumption was reasonably demonstrated in some studies, which showed that CH was limited in the lower body when sympathicotomy was expanded to R7 and thoracic sympathicotomy improved CH in the trunk when CH developed after sympathicotomy (10,28,29). Therefore, we designed an expanded sympathicotomy technique to reduce CH.…”
Section: Discussionmentioning
confidence: 74%
“…In regard to safety of the expanded sympathicotomy, the sympathetic chain can be injured in the lower thorax when a severe adhesion is dissected in thoracic surgery or when an extrapleural procedure or pleurectomy is performed; however, no major complications have not been reported due to injury of the sympathetic chains in the lower thorax, except for the splanchnic nerve (30). In addition, the level of sympathicotomy ranged from R1 to R8 in a few studies (10,28,29). Because of these, we assumed that the sympathetic chain in the lower thorax could be cauterized without any major complications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 11 ] Many recent studies aimed to explore various interventions to relieve the severe symptoms of hyperhidrosis by disruption of the targeted ganglia, either surgical or by laser photocoagulation. [ 12 , 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…The severe hyperhidrosis in the trunk and hands interfered with the patient's everyday activities, and medical treatment failed, leading to the selection of surgical sympathetic blockade for treatment. Trunk is innervated by ipsilateral sympathetic efferent fibers from segments T4 to T12 (2) and previous studies have reported successful management in the trunk with sympathetic blockade (T4-T7) via ablation or botulinum toxin (1,3,6,8). We think that the ranges of sympathotomy for truncal compensatory hyperhidrosis are not defined yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, postoperative compensatory hyperhidrosis is a challenging complication that can cause patients to regret undergoing surgery and lead to a surgeon's reluctance to choose surgery as the first treatment option for primary hyperhidrosis, especially craniofacial hyperhidrosis (1,3). Compensatory hyperhidrosis most commonly affects the trunk after sympathetic blockades (5,6). Herein, we present a rare case of a successful sympathotomy for severe compensatory hyperhidrosis in the trunk caused by traumatic cervical spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%